Will Digital Inclusive Finance Make Economic Development Greener? Evidence From China - Li, Guangqin; Fang, Xubing; Liu, Maotao (Frontiers in Environmental Science, 2021)
AAccurately assess the driving effect of Digital Inclusive Finance (DIF) on green economic growth, better implement DIF-related policies, and promote the development of green economy. Based on the urban panel data from 2011 to 2018 and the DIF index, this paper investigates the impact of DIF on the economic green development and its internal mechanism. The results show that: there is a significant positive U-shaped non-linear relationship between DIF and green development; Through the robustness test of the threshold model, instrumental variable model (IV), and system generalized method of moments model (SYS-GMM), the results are still valid; The mechanism research shows that the DIF can indirectly promote China's the green development by the co-agglomeration degree of producer services and optimizing and the upgrading of industrial structure. This study provides policy implications for developing countries around the world to achieve green development by promoting DIF level.